REGULATION OF SOCS EXPRESSION: A PROMISING TARGET FOR ANTI-HIV RESEARCH - SARFARAZ ALAM; MANSI SHRIVASTAVA; LK DWIVEDI (International Journal of Pharma and Bio Sciences, 2012)
Suppressor of Cytokine Signaling (SOCS) proteins are the negative regulators of cytokine signals as a natural precaution to prevent excessive responses that could cause damage to body tissues. However, their over expression is suggested to inhibit the anti-proliferative and antiviral activities of Interferon (IFN). Several viruses including HIV-1 have been reported to exploit the SOCS proteins for minimizing the activity of Interferon (IFN). Hence, the attempts to regulate the SOCS expression may be a novel roadblock into viral proliferation and pathogenesis. Present review is an effort to summarize the SOCS contribution in viral contagion and future therapeutic prospects against HIV-1. Running Head- Aberrant SOCS expression: a target for anti-HIV research